Vitellogenesis in Varroa-Jacobsoni, a parasite of honey-bees - Steiner, Josefina; Diehl, Peter-Allan; Vlimant, Michèle (My University, 1995)
Reproduction in Varroa jacobsoni occurs only in cells of the capped honey bee brood. Female mites were sampled at different times after cell sealing and ovaries containing a vitellogenic oocyte of the first gonocycle were examined under an electron microscope. It was found that the cytoplasmic connection between the lyrate organ and the oocyte persists far into the vitellogenic growth phase. In addition, a large amount of yolk material is taken up from the haemolymph. All ultrastructural features characteristic of vitellogenesis, such as microvilli, coated pits, vesicles and growing yolk platelets, are present. If more than four Varroa females live in an overcrowded brood cell, they appear to be in stress conditions and their vitellogenic oocytes may become atretic. Alterations typical for oocyte degradation and oosorption were observed in such situations.
Keywords: VARROA; BEE PARASITE; ULTRASTRUCTURE; VITELLOGENESIS; OOSORPTION